Differences in hemoglobin levels before and after administration of iron supplements and eggs to female students - Anesti, Fadhilah Dwi (ELECTRON (Journal of Science and Technology), 2024)
Anemia is a condition characterized by a decrease in the number of red blood cells or hemoglobin concentration, which impairs the blood’s capacity to transport oxygen to body tissues. The high prevalence of anemia is influenced by several factors, including inadequate intake of iron and other essential nutrients such as vitamins A, C, folate, riboflavin, and vitamin B12. Iron requirements can be fulfilled through the consumption of animal-based foods, which provide highly bioavailable iron, or plant-based foods, which contain iron with lower absorption rates. This study aimed to determine the differences in hemoglobin levels before and after the administration of iron tablets and eggs among female students at SMA N 1 Segedong, located in the working area of the Segedong Community Health Center, Mempawah Regency. A quasi-experimental design with a non-randomized one-group pretest–posttest approach was employed. The sample was selected using purposive sampling. Data were analyzed using univariate and bivariate analyses with the Chi-square test. The results showed a significant difference in hemoglobin levels before and after iron tablet administration (p = 0.001) and before and after egg consumption (p = 0.000). In conclusion, there were significant differences in hemoglobin levels following the administration of iron tablets and eggs among female students at SMA N 1 Segedong.